The cult of glory: national myth and the idea of Global Maritime Fulcrum in Indonesia's foreign policy, 2014–2019. (3rd July 2021) - Rosyidin, Mohamad
ABSTRACT : This article aims to explain the idea of Global Maritime Fulcrum (GMF) by applying the concept of national myth. In his first term as Indonesia's president, Joko Widodo, committed to restoring the country's status as a maritime power, based his government's foreign policy strategy on the glorious story of the Srivijaya and Majapahit kingdoms that ruled from the seventh to sixteenth centuries ad . Existing literature on the GMF in Indonesia's modern-day foreign policy fails to address the question of how the story has influenced the political elites in dictating foreign policy agenda. This article argues that the idea of the GMF comes from the recreation of national myth from Indonesia's pre-modern era. Furthermore, Jokowi's administration uses the past glory to bring about collective identity in order to restore the country's status through the GMF framework.